1999
DOI: 10.1038/sj.bmt.1701604
|View full text |Cite
|
Sign up to set email alerts
|

Increasing mixed haematopoietic chimaerism after BMT with total depletion of CD4+ and partial depletion of CD8+ lymphocytes is associated with a higher incidence of relapse

Abstract: Summary:In this study we analysed the incidence and clinical impact of the persistence of host haemopoiesis (mixed chimaerism, MC) after allogeneic BMT in 35 consecutive patients with haematologic malignancies using a total CD4؉ cell-depleted graft with an adjusted dose of CD8 ؉ cells (1 ؋ 10 8 /kg). Chimaerism was assessed by PCR amplification of VNTRs in 30 evaluable patients: 19 non-CML and 11 CML cases which were also evaluated for the BCR-ABL transcript by RT-PCR. All but one had complete engraftment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
18
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 12 publications
0
18
1
1
Order By: Relevance
“…1,2,10,13 As for the relapse of leukemia, several studies have suggested that MC after allogeneic HCT was correlated with relapse in chronic myelogenous leukemia (CML). [14][15][16][17] In cases of acute leukemia, the findings were not consistent among studies, with some studies suggesting a correlation of MC with relapse [18][19][20][21] while others failed to show such a correlation. 6,8,9,14,17,22 In most studies, the timing of the assay of HpC after HCT was not controlled and the data were analyzed retrospectively.…”
mentioning
confidence: 45%
See 2 more Smart Citations
“…1,2,10,13 As for the relapse of leukemia, several studies have suggested that MC after allogeneic HCT was correlated with relapse in chronic myelogenous leukemia (CML). [14][15][16][17] In cases of acute leukemia, the findings were not consistent among studies, with some studies suggesting a correlation of MC with relapse [18][19][20][21] while others failed to show such a correlation. 6,8,9,14,17,22 In most studies, the timing of the assay of HpC after HCT was not controlled and the data were analyzed retrospectively.…”
mentioning
confidence: 45%
“…[14][15][16][17] In cases of acute leukemia, the findings were not consistent among studies, with some studies suggesting a correlation of MC with relapse [18][19][20][21] while others failed to show such a correlation. 6,8,9,14,17,22 In most studies, the timing of the assay of HpC after HCT was not controlled and the data were analyzed retrospectively. 2,[9][10][11][17][18][19] In a series of 163 consecutive adult patients who underwent allogeneic HCT in our hospital, we monitored the status of HpC using a sensitive PCR-based method at monthly intervals in a prospective manner.…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…[1][2][3][4][5] Several studies suggested that MC after allogeneic BMT may correlate with relapse in chronic myelogenous leukemia (CML). [4][5][6][7][8] These studies showed that increasing proportions of recipient cells over time are highly associated with subsequent relapse while low levels of persisting recipient cells are not associated with an increased risk of relapse. In cases of acute leukemia, however, the significance of MC as a predictive marker for relapse is less clear.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Such mixed chimerism (MC) in the hematopoietic system was suggested to be a marker of immune tolerance as well as closer tissue matching between the donor and recipient on the basis of a decreased incidence of graftversus-host disease (GVHD). [1][2][3][4][5] Several studies suggested that MC after allogeneic BMT may correlate with relapse in chronic myelogenous leukemia (CML).…”
mentioning
confidence: 99%